The Effect Of Owner’S Education, Business Age, Business Scale And Accounting Training On The Use Of Umkm Accounting Information - Amin Nudin, Rikat; Wuryani, Eni; Isahak, Mohamad Shahril (International Environmental Conferrence on Biosustainability Advancement, 2024)
This study aims to determine the effect of the owner's or manager's educational background, business age, business scale and accounting training on the use of MSMEs accounting information in Kampung Pia Pasuruan. This type of research is quantitative. The population in this study was 50 MSMEs and the sampling technique used a saturated sample. The data analysis method used in this study is multiple linear regression analysis with the help of IBM SPSS 26. The results of this study indicate that the education of the owner or manager has a positive effect on the use of accounting information. The results of this study also show that business age, business scale and accounting training have no effect on the use of accounting information